ANALISIS SISTEM PENGENDALIAN INTERN PEMERINTAH DALAM PELAKSANAAN PENCAIRAN ANGGARAN BELANJA NEGARA PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA JAKARTA IV - Yogi Kusmandhani (Master in Accounting Program, 2014)
This study aims to obtain an overview as well as to analyze the effectiveness and obstacles that occured in the implementation of Government Internal Control System (SPIP) in the process of state-budget expenditure disbursement in Treasury Office (KPPN) of Jakarta IV. The study also tried to identify the mechanisms of institutional isomorphism that emerge in the implementation of SPIP. The data collection techniques exercised were interviews, observation, documentation, and questionnaires. Analysis of data using Miles & Huberman model consists of three stages i.e. data reduction, data presentation, and conclusion. Based on the results of data analysis, it is concluded that the implementation of SPIP in KPPN Jakarta IV has been effective but still have to make improvements in several parameters. Institutional Isomorphism mechanisms that occurred in the implementation of SPIP were coercive isomorphism and normative isomorphism.